A retrospective comparison of venetoclax alone or in combination with an anti-CD20 monoclonal antibody in R/R CLL - Mato, Anthony R. (Blood Adv, 2019)
Venetoclax (VEN) is approved for relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL) as monotherapy (VENmono) or in combination with rituximab. Whether VEN plus anti-CD20 (VENcombo) is superior to VENmono is unknown. We conducted a multicenter, retrospective cohort analysis comparing 321 CLL patients treated with VENmono vs VENcombo across the United States and the United Kingdom. We examined demographics, baseline characteristics, dosing, adverse events, response rates, and outcomes. The primary endpoints were progression-free survival (PFS) and overall survival (OS), estimated by Kaplan-Meier method, in patients treated with VENmono vs VENcombo. Univariate and bivariate analyses were performed with COX regression. Three hundred twenty-one CLL patients were included (3 median prior treatments, 78% prior ibrutinib). The overall response rates (ORRs) were similar (VENmono, 81% ORR, 34% complete remission [CR] vs VENcombo, 84% ORR, 32% CR). With a median follow-up of 13.4 months, no differences in PFS and OS were observed between the groups. In unadjusted analyses, the hazard ratios (HRs) for PFS and OS for VENmono vs VENcombo were HR 1.0 (95% confidence interval [CI], 0.6-1.8; P = .7) and HR 1.2 (95% CI, 0.6-2.3; P = .5), respectively. When adjusting for differences between the cohorts, the addition of an anti-CD20 antibody in combination with VEN did not impact PFS (HR, 1.0; 95% CI, 0.5-2.0; P = .9) or OS (HR, 1.1; 95% CI, 0.4-2.6; P = .8). We demonstrate comparable efficacy between VENmono and VENcombo in a heavily pretreated, high-risk, retrospective cohort, in terms of both response data and survival outcomes. Prospective studies are needed to validate these findings.